Old Tip vs. the Sly Fox : the 1840 election and the making of a partisan nation - Ellis, Richard (Richard J.) (American presidential elections., 2020)
"The 1840 election is best known for giving us the most famous presidential campaign slogan in history: "Tippecanoe and Tyler too." Featuring log cabins, sly songs, and misleading rhetoric, it is an election usually seen as determined by campaign tactics designed to dupe the gullible masses. While we are tempted to attribute victory to the cleverness of the winning campaign and defeat to the missteps of the losing campaign, a broader perspective on the showdown between the Democratic incumbent Martin Van Buren and Whig nominee William Henry Harrison reveals other factors at work-especially the fluctuating economy and growing antislavery sentiment, which saw the rise of the Liberty Party and the fall of Henry Clay's bid for the nomination. Richard J. Ellis also shows that understanding 1840 requires looking past the dramatic presidential election to the numerous state and congressional elections that took place between 1836 and 1840, culminating in the bitter fight for the Whig nomination and a record voter turnout in the Old Tippecanoe's unlikely victory. According to Ellis, the election of 1840 should be remembered not for log cabins and cider barrels, but for the Whig Party's historic convention, which was the first time a major political party selected, rather than anointed, its nominee at a national convention. Thoroughly researched and comprehensive in scope, Old Tip vs. The Sly Fox is a nuanced look at an election that helped define modern presidential campaign tactics and was a formative step in the making of our partisan nation."--